Studi Karakteristik Fondasi Pelat Tipis Dengan Pengaku Tiang “+” Pada Tanah Granuler Melalui Uji Eksperimen Dan Analisis Pemodelan Menggunakan Software Abaqus - Syarif, Firman; Adi, Agus Darmawan; Saputra, Ashar (UIR Press, 2017)
[EN] The amount of damage that happened in Indonesian road is the impact of high traffic load exceeds the carrying capacity of the pavement. To reduce the problems that occur on the pavement the good systems of pavement are built, various studies conducted to produce a creative innovation in order to evaluate and improve the performance of the pavement system. this study has developed a new system of foundation with pile